Two field BPS solutions for generalized Lorentz breaking models - Dutra, Alvaro de Souza [UNESP]; Hott, M.; Barone, F. A. (American Physical Soc, 2006)
In this work we present nonlinear models in two-dimensional space-time of two interacting scalar fields in the Lorentz and CPT violating scenarios. We discuss the soliton solutions for these models as well as the question of stability for them. This is done by generalizing a model recently published by Barreto and collaborators and also by getting new solutions for the model introduced by them.